Effects of Altering Dietary Acid-Binding Capacity-4 with Specialty Soy Protein Sources or Acidifiers on Nursery Pig Performance and Fecal Dry Matter - Ethan B. Stas; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Robert D. Goodband; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 300 pigs (241 × 600 DNA; initially 13.2 lb) were used to evaluate the effects of altering the dietary acid-binding capacity-4 (ABC-4) with specialty soy protein sources or acidifiers on nursery pig performance and fecal dry matter (DM). At weaning, pigs were allotted to 1 of 5 dietary treatments. There were 5 pigs per pen and 12 replications per treatment. Pigs were fed experimental diets in two phases with phase 1 fed from d 0 to 10 post-weaning followed by phase 2 from d 10 to 24. Diets were formulated with increasing ABC-4. A single low ABC-4 diet was formulated to 200 and 250 meq/kg in phase 1 and 2, respectively. The low ABC-4 diet utilized 0.38% fumaric acid, 0.36% formic acid, and specialty soybean meal (AX3 Digest; Protekta; Newport Beach, CA) at 9.38 and 7.50% of the diet in phase 1 and 2, respectively. Two medium ABC-4 diets were formulated utilizing two different strategies. In the first medium ABC-4 diet, specialty soybean meal was replaced with enzymatically treated soybean meal on an SID Lys-basis and resulted in an ABC-4 level of 290 and 322 meq/ kg for phase 1 and 2, respectively. In the second medium ABC-4 diet, acidifiers were removed resulting in an ABC-4 level of 271 and 321 meq/kg for phase 1 and 2, respectively. In the high ABC-4 diet, specialty soybean meal was replaced with enzymatically treated soybean meal and the acidifiers were removed, resulting in ABC-4 values of 362 and 394 meq/kg for phase 1 and 2, respectively. In addition, the high ABC-4 diet, but with added pharmacological levels of Zn from ZnO served as a control diet. Following phase 2, all pigs were fed a common diet until d 38 of the study. Increasing ABC-4 levels tended to decrease (linear,P= 0.062) the ADG during the experimental period. Pigs fed increasing ABC-4 diets had poorer (linear,P≤ 0.043) F/G during the experimental period (d 0 to 24) and overall (d 0 to 38). Increasing ABC-4 levels also decreased (linear,P≤ 0.005) fecal DM on d 10 and 24. Pigs fed diets containing pharmacological levels of Zn from ZnO had improved (P≤ 0.047) BW, ADG, ADFI, and F/G during the experimental period (d 0 to 24) but poorer (P= 0.005) ADG and F/G during the common period (d 24 to 38), compared to pigs fed diets not containing ZnO. Ultimately, this resulted in no benefit from ZnO for the overall study (d 0 to 38). There were no differences between the two medium ABC-4 levels for the growth performance. However, pigs fed the medium ABC-4 diet based on specialty soy protein replacement had increased (P= 0.003) fecal DM on d 10 compared to the medium ABC-4 diet where acidifiers were removed. In conclusion, as dietary ABC-4 increased from 200 to 362 meq/kg in phase 1 and 250 to 294 meq/kg in phase 2, pigs had linearly decreased growth performance and fecal DM. The results of this study suggest a low ABC-4 diet can be utilized to improve growth performance and fecal consistency in diets without pharmacological Zn. Additionally, there were no differences between the medium ABC-4 diets for growth performance, suggesting the decreased performance was due to an increase in ABC-4 level and not a change in ingredients.
Keywords: acid-binding capacity; specialty soy protein; acidifiers; nursery pigs